Optimization of cultural conditions using response surface methodology and modeling of indole-3-acetic acid production by Saccharothrix texasensis MB15. (January 2022) - Benadjila, Abderrahmane; Zamoum, Miyada; Aouar, Lamia; Zitouni, Abdelghani; Goudjal, Yacine
Abstract: This study aimed to develop a low-cost medium based on wheat waste (leaves and roots) to enhance Indole-3-Acetic Acid (IAA) production by the actinobacterial strain Saccharothrix texasensis MB15, using the Response Surface Methodology (RSM). Among eighteen endophytic or rhizospheric actinobacterial strains, Saccharothrix texasensis MB15 secreted high levels of IAA under standard cultural conditions. A Placket-Burman screening design was conducted to estimate the composition of low-cost medium and cultural conditions for S . texasensis MB15. Three factors, l -tryptophan, leaves extract, and inoculum quantity, respectively, showed a significant effect on IAA production by S . texasensis MB15. The RSM optimization step, for the three main factors, showed that improvement of IAA production was very significant, passing from 47 μg/ml within 120 h to more than 148 μg/ml within 96 h under RSM optimized conditions. From RSM analysis, the amounts of produced IAA were increased to an overall 2.65-fold in fermentation liquor, with a coefficient of determination R 2 of 0.993, which indicates that 99.30% of the variability in the response can be accounted for by the model. This is the first paper reporting RSM-based medium optimization of IAA by S . texasensis MB15, isolated from the hypersaline soil in an arid region of Algeria, exploring organic wastes. Graphical abstract: Image 1 Highlights: Indole-3-acetic acid production by the strain Saccharothrix texasensis MB15. Valuation of wheat wastes as fermentation medium. Optimization of cultural conditions to enhance the phytohormone production. Increases of IAA production by 265%. Mathematical modeling of biological production of IAA for sustainable agriculture.